Manufacturing of duplex stainless steel using local material ferronickel on laboratory scale - Ade Bagdja; Riyan Marlina (Prosiding SNTTM, 2025)
The study aims to manufacture a duplex stainless steel in laboratory scale using local ferronickel as the main alloying material. The melting process was carried out using the Electric Arc Furnace (EAF) method using three variations of material composition: (1) Fe-Ni 40%, Fe 35%, Cr 25%; (2) Fe-Ni 42%, Fe 33%, Cr 25%; (3) Fe-Ni 38%, Fe 33%, Cr 25%. Tests carried out included microstructure, Vickers hardness, and chemical composition. Microstructure testing showed that all specimens formed two main phases, namely ferrite and austenite. Hardness testing of the three specimens: (1) 217.70 HV; (2) 239.22 HV; (3) 221.52 HV. Chemical composition testing showed that all specimens had a Cr content of 19.7% - 22.3% and Ni 8.52% - 9.75%. Mapping of the chemical composition of each test specimen on the Schaeffler diagram shows that all specimens are in the duplex stainless steel region. Furthermore, specimen 2 shows the best phase balance with the highest hardness value of 239.22 HV. This study proves that local ferronickel can be used as an alternative alloying material in the production of duplex stainless steel.